Nonstrangulating intestinal infarctions associated with Strongylus vulgaris: Clinical presentation and treatment outcomes of 30 horses (2008–2016). (27th November 2017) - Pihl, T. H.; Nielsen, M. K.; Olsen, S. N.; Leifsson, P. S.; Jacobsen, S.
Summary: Background: Strongylus vulgaris is re‐emerging in horses kept under surveillance‐based parasite control regimens. Information on nonstrangulating intestinal infarction associated with S. vulgaris is needed to improve recognition of the condition. Objective: To describe the typical clinical presentation, laboratory findings, gross pathology, treatment and outcome of horses with nonstrangulating intestinal infarction. Study design: Retrospective case series. Methods: Nonstrangluating intestinal infarction was diagnosed in 30 horses with a localised intestinal infarction with concurrent signs of S. vulgaris migration and no signs of intestinal strangulation or enterocolitis. Data were obtained from medical records in the period 2008–2016. Long‐term follow‐up information was obtained by telephonic interviews. Levels of S. vulgaris ‐specific antibodies were retrospectively assessed. Associations between nonstrangulating intestinal infarction and selected variables were evaluated using Fisher′s exact and Mann–Whitney U tests. Results: The most consistent findings at admission were mild colic of >24 h duration without signs of shock or strangulated intestine, increased peritoneal fluid WBC (>5 × 10 9 /L), increased serum amyloid A (SAA) concentration and a positive S. vulgaris ‐specific antibody titre. Medical treatment was attempted in nine horses with none surviving. Exploratory laparotomy was performed in 21 horses. Eleven horses were subjected to euthanasia intraoperatively due to the presumed poor prognosis. Of the nine horses, three (33%) undergoing intestinal resection survived to discharge. The surviving horses were alive and returned to athletic function for at least 2 years following discharge. Main limitations: Only nine of the 30 horses underwent resection of the infarcted intestine, and the prognosis for surgical intervention in nonstrangulating intestinal infarction is, therefore, difficult to estimate. Conclusions: In areas where S. vulgaris is prevalent, nonstrangulating intestinal infarction should be considered as a differential diagnosis in horses presenting with mild colic and peritonitis. Survival of nonstrangulating intestinal infarction is possible in cases where surgical intervention with resection of the infarcted intestine is feasible. The summary is available in Spanish ‐ see Supporting Information.